Sustainability of Food Packaging: Hygienic, Low-cost, Attractive Design, and Environmental-friendly - Saptaria, Lina; Shobirin, Rizky Arief (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.36, 2020)
This paper is being purposed to expose the main factors inside packaging to emphasize market value of the product inside the package. Mainly, the packaging is proposed to protect the product inside. It could be divided into several parts, including primary packaging, secondary packaging, and tertiary packaging. Packaging does keep the product long in good condition, but in the view of the packaging company can also reduce the profits of a company. And also, selection of the right material needs to be considered to maintain the hygiene and safety of food and beverage products. Equally important, the design of an attractive package is also very influential on consumers' interest to buy the product. Therefore, the plastic packaging is not only seen from the level of hygiene in keeping the product safe, using inexpensive materials, attractive designs, but also environmentally friendly.